La festa della Porchetta a Bologna: nuove prospettive di indagine (II) - Vallieri, Lorena (Drammaturgia, 2022)
The essay reconstructs some episodes of the Feast of the Porchetta. A civic event of long history that, at least from the end of the Sixteenth Century, used different artistic, literary, musical and spectacular typologies to convey the ambitions of the Senatorial aristocracy of Felsina. It was also a highlight of the ephemeral state and allowed Bologna to be assigned its rightful place among the European capitals of the spectacle of the Ancient Regime. An extensive unpublished documentation preserved at the Archivio di Stato di Bologna, including two contracts for the construction of theatres and workshops for the fairs of 1627 and 1702, and an icnography of 1697, testify to an unexpected organizational punctuality.